2010
DOI: 10.1186/1475-2875-9-374
|View full text |Cite
|
Sign up to set email alerts
|

Protecting the malaria drug arsenal: halting the rise and spread of amodiaquine resistance by monitoring the PfCRT SVMNT type

Abstract: The loss of chloroquine due to selection and spread of drug resistant Plasmodium falciparum parasites has greatly impacted malaria control, especially in highly endemic areas of Africa. Since chloroquine removal a decade ago, the guidelines to treat falciparum malaria suggest combination therapies, preferentially with an artemisinin derivative. One of the recommended partner drugs is amodiaquine, a pro-drug that relies on its active metabolite monodesethylamodiaquine, and is still effective in areas of Africa,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
59
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(64 citation statements)
references
References 13 publications
3
59
2
Order By: Relevance
“…The pfcrt SVMNT haplotype is associated with AQ resistance; it is postulated to carry a lower fitness cost than the CVIET haplotype and to persist among the parasite population even after the removal of drug pressure, potentially jeopardizing the effectiveness of artesunate-AQ, which is widely used in west Africa (37,38). Surprisingly, this haplotype, which is usually found in South America and parts of Asia, was detected in adult samples from Luanda in 2007 (15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pfcrt SVMNT haplotype is associated with AQ resistance; it is postulated to carry a lower fitness cost than the CVIET haplotype and to persist among the parasite population even after the removal of drug pressure, potentially jeopardizing the effectiveness of artesunate-AQ, which is widely used in west Africa (37,38). Surprisingly, this haplotype, which is usually found in South America and parts of Asia, was detected in adult samples from Luanda in 2007 (15).…”
Section: Discussionmentioning
confidence: 99%
“…The different pfcrt mutant haplotypes have a consistent geographical distribution: the CQR haplotype CVIET is predominant in southeast Asia and Africa, whereas the AQ-resistant (AQR) haplotype SagtVMNT is predominant in Asia and South America, and StctVMNT, from South America, is very rare in Africa (16).The wild-type haplotype CVMNK is widespread (6,16,29,38). A recent study reported the presence of the StctVMNT haplotype of pfcrt in Angola, but this has not yet been verified by others (15,37). Polymorphisms in the parasite protein Pgh-1, encoded by pfmdr1, are thought to modulate resistance to drugs such as quinine, mefloquine, halofantrine, artemisinin, lumefantrine, CQ, and AQ (1,21,32,38).…”
mentioning
confidence: 99%
“…7 Recent data confirm the appearance in neighboring Tanzania 8 and Angola 9 of the pfcrt haplotype SVMNT, which may confer resistance to amodiaquine 1,10 and herald failures of ASAQ. 11 Additionally, the haplotype SVIET has been reported from Kinshasa in 2000, although it is of unclear biological significance. 12 To inform current and future guidelines on antimalarial use in Central Africa, we conducted a cross-sectional survey of pfcrt haplotypes in the DRC.…”
mentioning
confidence: 99%
“…19 Parasites with the SVMNT haplotype are highly resistant to MDAQ, but only moderately resistant to CQ, whereas P. falciparum clones with the CVIET haplotype are moderately resistant to MDAQ and highly resistant to CQ. These data, coupled with observations on the historical use of AQ in India, Brazil, and other malaria-endemic areas of the Americas and South Pacific suggest that AQ had an early and prominent role in the selection of drug-resistant SVMNTtype parasites 20 ; it is not clear through which mechanism the different pfcrt haplotypes interact with AQ, MDAQ, or CQ.…”
mentioning
confidence: 99%